Meldonium and neuroprotection. Theory, experiment and clinical practice. - Muslin, V. P.; Pohorielov, O. V. (Medicni Perspektivi, 2018)
In this review the possibilities of correction of brain metabolism in cases of acute cerebral ischemia (ACI) under using meldonium were considered. The biochemical specificity of this remedy in Krebs cycle, influence on cerebral glycolysis, by activating the stress-limiting system, lactate-glutamate and glycogen mechanisms of the biochemical shunt were discussed. There were described effects of meldonium on cerebral processes that can be conditionally separated into carnitine-dependent and carnitine-independent. Results of experimental research of meldonium proved certain metabolic influence on NMDA receptor system. The analysis of the results of experimental and clinical studies makes it possible to consider that any neuroprotective pharmacological remedies have comparatively low efficacy in cases of acute cerebral ischemia. Meldonium effects do not differ from others similar neuroprotective remedies in such cases. In experimental works meldonium can improve metabolism in central nervous system (CNS) and would be considered as a pharmacological remedy that creates conditions for optimizing and economizing metabolism of the CNS. Meldonium in experimental conditions (predominantly in mice) can help to optimize metabolism of glucose in the CNS, especially aerobic glycolysis that creates opportunities to form economizing way of the basic metabolism. In target usage of the drug in the experiment a "smooth exit" from the ischemic state and decrease of the negative effects of oxidative stress is possible. Possible areas and clinicaly unproved efficiency of the drug in ACI should be considered while planning therapy of ACI and at the stages of rehabilitation.